2018
DOI: 10.1097/md.0000000000010095
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma of the supraglottis with a distinct presentation

Abstract: Rationale:Salivary duct carcinoma (SDC) is a rare and aggressive subtype of salivary gland carcinoma that histologically resembles in situ and invasive ductal carcinoma of the breast. We present the first case of advanced SDC of the minor salivary gland arising from the supraglottis and review the literature on the clinicopathologic characteristics and prognosis of SDC.Patient concerns:A 59-year-old male patient with progressive difficulty in swallowing and a muffled voice for 2 months.Diagnoses:The patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…High-grade SDC is histopathologically characterized by proliferation of dysplastic cells containing large round to oval nuclei with conspicuous nucleoli and rich eosinophilic cytoplasm, occasionally accompanied by comedo necrosis, which resembles high-grade breast carcinoma. The immunohistochemical characteristics of SDC cells include positive staining for human epidermal growth factor receptor (HER) 2, AR and CK7 ( 2 , 4 ). Since most salivary gland malignancies have positive immunoreactivity for CK7, immunoexpression of this protein may provide valuable information to differentiate primary salivary gland carcinomas from metastatic tumors ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…High-grade SDC is histopathologically characterized by proliferation of dysplastic cells containing large round to oval nuclei with conspicuous nucleoli and rich eosinophilic cytoplasm, occasionally accompanied by comedo necrosis, which resembles high-grade breast carcinoma. The immunohistochemical characteristics of SDC cells include positive staining for human epidermal growth factor receptor (HER) 2, AR and CK7 ( 2 , 4 ). Since most salivary gland malignancies have positive immunoreactivity for CK7, immunoexpression of this protein may provide valuable information to differentiate primary salivary gland carcinomas from metastatic tumors ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although complete surgical resection and ipsilateral neck dissection followed by postoperative radiation comprise the standard treatment for SDC ( 10 - 12 ), the reported survival rate is 43% for the 5-year disease-specific survival and 36% for the disease-free survival ( 2 , 13 ). Johnston et al reported that 37.5% of the patients with local and regional recurrence of SDC showed distant metastases ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations